Customers' perceptions on the dispute resolution clauses in Islamic Finance contracts in Malaysia - Oseni, Umar Aimhanosi; Adewale, Abideen Adeyemi; Mohd. Zain, Nor Razinah (2015)
This empirical legal study examines the perceptions of retail customers on the dispute resolution clauses contained in the governing law and jurisdiction clauses in Islamic finance contracts in Malaysia. Since Islamic financial institutions and their customers are more likely to opt for litigation in the event of a dispute, this study explores ways of providing for unambiguous dispute resolution clauses that are well understood by the parties. Such clauses are expected to incorporate effective dispute resolution processes such as mediation and arbitration through a multi-tiered mechanism. Primary data collected through survey questionnaire administered on 160 Islamic bank customers is analysed using both factor analysis and structural equation modelling via the IBM SPSS version 20 software. The empirical legal study reveals that there is a statistically significant difference among two major groups of customers based on their legal understanding of the dispute resolution clauses in Islamic finance contracts. The group that sought further clarification has a statistically significant path from provision of legal clauses to legal understanding and indirectly to their choice of dispute resolution channels. It therefore follows that there is a need to provide for more effective clauses that allow for mediation and arbitration in the governing law and jurisdiction clauses of Islamic finance contracts in Malaysia. Such alternative dispute resolution processes can be structured in a multi-tiered manner that will only allow for litigation as a last resort. This will allow Islamic financial institutions and their customers to make informed decisions about the best option for effective dispute management.